La producción de nuevas naturalezas en la alta Amazonía peruana (1940-1981) y las tesis de Ester Boserup - Bedoya-Garland, Eduardo (2023)
The purpose of this work is to describe the historical, population, economic, and environmental conditions that led to the expansion of the agricultural and demographic frontier in the Peruvian high jungle, particularly in the Alto Huallaga basin, during the decades spanning from 1940 to the early 1980s. The text describes and analyzes how the dynamics of demographic frontier expansion, through highland-origin settler farmers, exerted intense pressure on natural resources, subsequent environmental degradation, and eventually regional demographic saturation. The migrant settlers continually reproduced their family units of production and consumption in frontier territories, thereby creating new natures and destroying others in the process. In this context, we aim to explore the links between demographic growth in the Alto Huallaga and the slash-and-burn agricultural systems that accompanied them, as well as the socio-environmental consequences and the ongoing feedback dynamics between these processes. In doing so, we put to the test the model of land use extensification and intensification proposed by economist Ester Boserup.